Salimos a la plaza!, difundiendo al mundo lo aprendido y experimentado en materia de género desde el aula de primaria - Arana Arrieta, Iñaki; Gómez Pintado, Ainhoa; Vizcarra Morales, María Teresa (Retos (Madrid), 2024)
The "Let's go out to the square" initiative is a formative research-action that was carried out with three groups of 6th grade primary school children in a town in the province of Gipuzkoa. It was an initiative to convey to society the concerns, complaints, opinions and proposals that had arisen in these groups of girls and boys after training on the gender perspective in physical and sporting activities. The aim of this action was to make public the reflections arising from a school, in an academic environment, and to give them power, transcendence and relevance. The final aim was to convey to society the concerns, complaints, opinions and proposals on gender made by this group of students, which are generally not listened to or heeded. In order to publicize their reflections on the inclusion of the gender perspective in physical activities and sports, the students experimented with different ways of dissemination: poster, triptych, opinion article and press conference. In this action research, documentary records, photographs, audio recordings and field notes were used to collect the information. The experience allowed the students to reflect and debate on the social situations they observed every day and to subsequently transfer their demands and proposals to their community, carrying out a transformative transfer task. The messages expressed surprised the teaching staff with their capacity to make demands and criticize. It can be concluded that the experience led them to become empowered in gender issues, fostering their growth as individuals and as active citizens, a feeling that was reinforced by the perception of support from their peers. La iniciativa "salimos a la plaza” es una investigación-acción formativa que se llevó a cabo con tres grupos de 6º de Educación Primaria de un colegio de una población guipuzcoana. El objetivo final era trasladar a la sociedad las inquietudes, quejas, opiniones y propuestas que sobre el género hace este grupo de alumnas y alumnos, y que generalmente son poco escuchadas y atendidas. Para hacer públicas sus reflexiones sobre la inclusión de la perspectiva de género en las actividades físicas y deportivas, el alumnado experimentó con diferentes modos de difusión: póster, tríptico, artículo de opinión y rueda de prensa. En esta investigación-acción se utilizaron registros documentales, fotografías, registros de audio y notas de campo para recoger la información. La experiencia vivida permitió al alumnado reflexionar y debatir sobre las situaciones sociales que observaban cada día y trasladar posteriormente sus demandas y propuestas a su comunidad, ejerciendo una labor de transferencia transformadora. Los mensajes expresados sorprendieron al profesorado por su capacidad reivindicativa y crítica. Se puede concluir que la experiencia les llevó a empoderarse en temas de género fomentando su crecimiento como personas y como ciudadanía activa, sentimiento que se vio reforzado por la percepción del apoyo de sus iguales.